Environmental monitoring applications to regional physical framework planning - Cabrido, Candido A. (1990)
There is a need to incorporate an environmental monitoring component in the physical framework plans of Philippine regions, considering the fast rate of environmental degradation in the country. Environmental monitoring will determine whether the level of resource exploitation and degradation is already exceeding acceptable limits or whether a course of action is meeting its targets. The resulting information generated by the monitoring system will provide a basis in revising and refining the physical framework plan. An approach for monitoring the environmental parameters of the regional physical framework plan is being proposed. The approach involves three actors, namely, the environmental agencies, NEDA regional Office, and NEDA Regional Coordination and Development Staff. the environmental parameters they are going to monitor include changes in land use quality, water quality, air quality, demographic aspects, and natural resource stock and productivity.